NILAI SOLIDARITAS DALAM TRADISI PERANG TIMBUNG PADA MASYARAKAT SUKU SASAK DI DESA PEJANGGIK LOMBOK TENGAH - Lalu Muhammad Hanafi, Hanafi; Yuliani (An-Nas, 2023)
This study aims to find out how the tradition of timbung war and what are the values ​​of social solidarity contained in society in the timbung war tradition. This study uses a qualitative method with a phenomenological approach. Data collection techniques through observation, interviews and documentation. The results in this study indicate that the timbung war tradition is one of the traditions passed down by our ancestors which was carried out from generation to generation from society to society. The aim of the timbung war is thatcan unite other pejanggik communities in one place and as a means of rejecting balaq and hoping for the blessings of the Almighty God, several processions in the timbung war, First, namely the Preparatory stage. Which consists of: deliberation and consensus, preparing the equipment to be used, and determining who will be the bride and groom in the Timbung war ritual event later. Second, the implementation stage. consisting of: taking holy water (aik sereat), reciting dutal or Lombok tripe, asking for permission to open the timbung war ceremony, reciting berzanzi as well as serrakalan, reciting prayers and remembrance together. Third, the closing stage. Consisting of: facial washing (seraup), and forehead marking (sesembek).